Clinical and pathogenetic features of ETV6 related thrombocytopenia with predisposition to acute lymphoblastic leukemia. - Melazzini, Federica; Palombo, Flavia; Balduini, Alessandra; De Rocco, Daniela; Marconi, Caterina; Noris, Patrizia; Gnan, Chiara; Pippucci, Tommaso; Bozzi, Valeria; Faleschini, Michela; Barozzi, Serena; Doubek, Michael; et al. (Haematologica, 2016)
ETV6-related thrombocytopenia (ETV6-RT) is an autosomal dominant thrombocytopenia that has been recently identified in a few families and has been suspected to predispose to hematological malignancies. To gain further information on this disorder, we searched for ETV6 mutations in the 130 families with inherited thrombocytopenia of unknown origin from our cohort of 274 consecutive pedigrees with familial thrombocytopenia. We identified 20 ETV6-RT patients from 7 pedigrees. They have 5 different ETV6 variants, including three novel mutations affecting the highly conserved E26 transformation-specific domain. The relative frequency of ETV6-RT resulted 2.6% in the whole case series and 4.6% among the families with known forms of inherited thrombocytopenia. The degree of thrombocytopenia and bleeding tendency of ETV6-RT patients were mild, but 4 subjects developed B-cell acute lymphoblastic leukemia during childhood, resulting in a significantly increased incidence compared to the general population. Clinical and laboratory findings did not identify any peculiar defects that can be used to suspect this disorder by routine diagnostic workup. However, at variance with most inherited thrombocytopenias, platelet size was not enlarged. In vitro studies revealed that patients megakaryocytes have defective maturation and impaired proplatelet formation. Moreover, ETV6-RT platelets have reduced ability to spread on fibrinogen. Since also the dominant thrombocytopenias due to mutations in RUNX1 and ANKRD26 are characterized by normal platelet size and predispose to hematological malignancies, we suggest that mutation screening of ETV6, RUNX1 and ANKRD26 should be performed in all the subjects with autosomal dominant thrombocytopenia and normal platelet size.